Research on monitoring college students’ sports psychological stress response and ideological and political education intervention based on biosensors - Jin, Zheyu; Wang, Qingbao; Meng, Fanjun; Xu, Jiuyang (Molecular & Cellular Biomechanics, 2024)
The current study aims to find out the psychosocial stress reactions of college students involved in sports and assess the impact of ideological and political education (I&PE) treatment based on the biosensor. Thus, we plan to use the biosensors including the heart rate monitors and the skin conductance devices to define the level of physiological stress in physical activities. The study also evaluates the extent to which the organizationally developed I&PE program effectively reduces psychological stressor by promoting resilience improvement, ideological awareness, and community support. This makes the research investigate the correlation between biosensor-based performance data on sports, stress and impressions of I&PE together with non-quantitative participants’ feedback. The outcomes of the study will identify stress management among college sports with potential biosensor use in educational contexts. This study fosters the sciences of sports psychology, interventional education, and mental health with a view of developing an all-inclusive student well-being framework.